Mapping political support in the 1990s: A global analysis - Hans-Dieter Klingemann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Over the past quarter century, an unprecedented and often unanticipated wave of democratization has spread over large parts of the world. While some skepticism is reasonable regarding both the level and durability of many of the new experiments of democratization, the direction and scope of these developments are largely beyond dispute. The main goal of this essay is to use an unprecedented body of comparative survey research to map patterns and forms of political support across a wide range of political conditions. While the goal is primarily descriptive, in the course of the descriptions interesting themes emerge, such as the finding that there are no major trends suggesting a decline in support for democracy as a form of government, neither de jure nor de facto, or that the fact of dissatisfaction does not imply danger to the persistence or furtherance of democracy. – – Die vorliegende Analyse soll den Grad der politischen Unterstützung der Bürger in globaler Perspektive beschreiben. Es wird nachgewiesen, daß die Bürger Einstellungen zur politischen Gemeinschaft, zur Demokratie als Regierungsform und zur Performanz der Demokratie voneinander trennen können. Die Verteilung dieser Einstellungen Mitte der neunziger Jahre wird für 38 Länder berichtet. Für eine kleinere Gruppe von Ländern können diese Einstellungen mit Daten aus dem Jahre 1990 verglichen werden. Als Ergebnis kann festgehalten werden, daß in den meisten Ländern ein relativ hohes Maß an Zustimmung zur Demokratie als Regierungsform festzustellen ist. Gleichzeit wird aber die Performanz der Demokratie negativ beurteilt. Es wird spekuliert, daß von der Gruppe der unzufriedenen Demokraten zukünftig Impulse für die Weiterentwicklung der Demokratie zu erwarten sind. Die Zeitvergleiche zeigen keine einheitlichen Trends an. Sie weisen vielmehr auf Entwicklungen hin, die in den unterschiedlichen Ländern in sehr unterschiedlicher Weise verlaufen.
Keywords: 300; Demokratie; Öffentliche Meinung; Welt